2017
DOI: 10.1186/s13063-017-2138-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of ibrutinib plus rituximab in front-line CLL (FLAIR trial): study protocol for a phase III randomised controlled trial

Abstract: BackgroundTreatment of chronic lymphocytic leukaemia (CLL) has seen a substantial improvement over the last few years. Combination immunochemotherapy, such as fludarabine, cyclophosphamide and rituximab (FCR), is now standard first-line therapy. However, the majority of patients relapse and require further therapy, and so new, effective, targeted therapies that improve remission rates, reduce relapses, and have fewer side effects, are required. The FLAIR trial will assess whether ibrutinib plus rituximab (IR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 9 publications
0
31
0
1
Order By: Relevance
“…Ibrutinib (PCI-32765), a specific and irreversible inhibitor of Bruton’s Tyrosine Kinase (BTK), is a small molecule orally administered, providing a selective and irreversible inhibition of BTK. In extensive studies, Ibrutinib has shown extremely promising results in front-line treatment as well as in relapsed/refractory (RR) CLLs 5,6 and is now tested in combination with other molecules 7 . However, cases of drug resistance have emerged 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Ibrutinib (PCI-32765), a specific and irreversible inhibitor of Bruton’s Tyrosine Kinase (BTK), is a small molecule orally administered, providing a selective and irreversible inhibition of BTK. In extensive studies, Ibrutinib has shown extremely promising results in front-line treatment as well as in relapsed/refractory (RR) CLLs 5,6 and is now tested in combination with other molecules 7 . However, cases of drug resistance have emerged 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…In CLL patients who are young and fit and lack deletion of 17p or TP53, current treatment guidelines recommend chemotherapy, commonly fludarabine, cyclophosphamide in combination with rituximab (FCR) as initial treatment based on the proven effectiveness of rituximab from several clinical trials ( 70 ). A recent Canadian study confirmed the tangible benefits in CLL by evaluating patients treated in the pre- and post-rituximab era ( 71 ).…”
Section: Clinical Impact Of Rituximab In B-cell Nhl Treatmentmentioning
confidence: 99%
“…The currently ongoing FLAIR phase III trial includes 754 CLL patients given either the current standard of care FCR, ibrutinib plus rituximab, ibrutinib plus venetoclax, or ibrutinib alone, potentially eliminating the need for more harmful chemotherapeutics in favor of more targeted therapeutics as the new standard of care ( 70 ). This study should also assess the benefit of the addition of rituximab to small molecule targeted therapies (in this case ibrutinib), which has been relatively understudied.…”
Section: Clinical Impact Of Rituximab In B-cell Nhl Treatmentmentioning
confidence: 99%
“…The FLAIR trial is randomizing untreated patients with CLL/ SLL in 1:1:1:1 ratio to FCR immunochemotherapy or three versions of ibrutinib therapy: ibrutinib monotherapy, IR, or VI. 51 Ibrutinib and venetoclax therapy can be continued for up to 6 years or discontinued if uMRD is attained. Both of these trials will be the first opportunity to compare VI and other venetoclax-based or ibrutinib-based novel chemotherapy free regimens to our standard chemotherapy strategies in the frontline setting.…”
Section: Venetoclax-based Regimens As Initial Treatment In Cll/sllmentioning
confidence: 99%